2015
DOI: 10.1098/rsif.2015.0821
|View full text |Cite
|
Sign up to set email alerts
|

Lift enhancement by bats' dynamically changing wingspan

Abstract: This paper elucidates the aerodynamic role of the dynamically changing wingspan in bat flight. Based on direct numerical simulations of the flow over a slow-flying bat, it is found that the dynamically changing wingspan can significantly enhance the lift. Further, an analysis of flow structures and lift decomposition reveal that the elevated vortex lift associated with the leading-edge vortices intensified by the dynamically changing wingspan considerably contributed to enhancement of the time-averaged lift. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…With these techniques, it has been shown that insects do exhibit time-varying changes in wing shape during flapping flight, and that these dynamic morphings are helpful in efficient aerodynamic force generation [16][17][18]. Generally, in-flight wing shapes of vertebrates are still largely unknown, with a few exceptions, particularly for bats [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…With these techniques, it has been shown that insects do exhibit time-varying changes in wing shape during flapping flight, and that these dynamic morphings are helpful in efficient aerodynamic force generation [16][17][18]. Generally, in-flight wing shapes of vertebrates are still largely unknown, with a few exceptions, particularly for bats [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [48] found that folding motion will increase both the time-averaged lift coefficient and instantaneous lift coefficient. Further research [49,50] revealed that folding motion can also increase the efficiency of lift production and reduce power consumption. Therefore, it may be inadequate to conduct the studies only under static and steady conditions.…”
Section: Comments On Research Modelsmentioning
confidence: 99%
“…Since then, certain unsteady mechanisms such as enhanced lift by the leading edge vortex (LEV) have been shown to be nearly ubiquitous in flapping flight, while other mechanisms such as clap and fling are only observed in certain insects operating at smaller length scales. Bats have also been shown to enhance lift by dynamically changing their wingspan [ 9 ].…”
Section: Introductionmentioning
confidence: 99%